Development of DNA and Oral Vaccines Against Chicken Anemia Virus - Moeini, Hassan (2010)
Chicken anemia virus (CAV) belongs to the genus Gyrovirus of Circoviridae family, which causes an economically important disease in the poultry industry worldwide. Commercially available vaccines against CAV infection which are based on nonattenuated virulent CAV propagated in chicken embryos or attenuated live vaccine cannot be used in chickens before 8 weeks of age and within 21 days of slaughter and sometimes spreading of the modified viruses to young chickens may cause disease. Therefore, the development of DNA and oral vaccines against this virus was considered in the current study. For development of DNA vaccine, the VP1 and VP2 genes of CAV were amplified and cloned into pBudCE4.1 to construct two DNA vaccines, namely, pBud-VP1, and pBudVP2-VP1. In vitro and in vivo studie showed that co-expression of VP1 with VP2 is required to produce the essential neutralizing form of VP1 to induce significant levels of antibody against CAV. Subsequently, the vaccines were tested in 2-week-old specific pathogen free (SPF) chickens which were inoculated with the DNA plasmid constructs by the intramuscular route. Serum antibody titers against CAV were determined 10 days after vaccination by ELISA. Chickens immunized with the DNA-plasmid pBudVP2-VP1 showed positive antibody titer (1853) against CAV. Furthermore, proliferation induction of splenocytes and also high serum levels of Th1 cytokines, IL-2 (78.2 pg/ml) and IFN-γ (534.5 pg/ml) were detected in the pBudVP2-VP1-vaccinated group indicating the induction of cell-mediated immune response in the vaccinated chickens. These results suggest that the recombinant plasmid pBudVP2-VP1 can be used as a potential DNA vaccine against CAV infection. To enhance CAV-specific immune responses, the use of the VP22 gene of Marek’s disease virus type-1 (MDV-1) linked to the CAV VP1 gene was also investigated. This was achieved by constructing a recombinant DNA plasmid, namely pBudVP2-VP1/VP22 encoding the fusion protein VP1/VP22 synchronously with the CAV VP2 and testing its effectiveness in specific pathogen free chickens. Chickens vaccinated with pBudVP2-VP1/VP22 exhibited a significant increase in antibody titers to CAV,VP1-stimulated proliferative induction of splenocytes and also higher levels of IL-2 and IFN-γ when compared to the chicken vaccinated with pBudVP2-VP1 (P<0.05). These observations showed that the MDV-1 VP22 is capable of enhancing the potency of DNA vaccine against CAV when fused with CAV VP1 gene expressing simultaneously with CAV VP2. In the second part of this study, Lactobacillus acidophilus (ATCC 53672) carrying the VP1 protein of CAV was used as live delivery vehicles for oral immunization against CAV. The binding domain of AcmA anchor protein of Lactococcus lactis MG1363 were used to display the VP1 protein of CAV on the surface of Lb.acidophilus. One and two repeats of the cell wall binding domain of acmA gene were amplified from L. lactis MG1363 genome and then inserted into co-expressionvector, pBudCE4.1 to construct plasmids pETacma1 and pETacma2, respectively. Thereafter, the VP1 gene of CAV was fused to the acmA sequences and the CAV VP2 gene was cloned into the second multiple cloning site on the same vector before transformation into Escherichia coli BL 21 (DE3). The expressed recombinant proteins were purified using a His-tag affinity column and mixed with a culture of Lactobacillus acidophilus. Whole cell ELISA and immunofluorescence assay showed binding of the fusion proteins containing the CAV VP1 protein on the surface of the cells. The lactobacilli cells carrying the VP1 protein were used to immunize SPF chickens through oral route. The presence of anti-CAV antibodies was detected by ELISA. The immunized chickens showed significantly (P<0.05) higher level of neutralizing antibody against CAV compared to those from the controls. VP1-specific proliferative response was also observed in splenocytes of the chickens after oral immunization. Furthermore, high levels of Th1 cytokines, IL-2 and IFN-γ were d tected in the immunized chickens. These results showed that the lactobacilli cells carrying the VP1 protein of CAV could induce immune response against CAV suggesting lactobacilli as live delivery vehicle for oral immunization purposes.